Analisis Faktor–Faktor yang Mempengaruhi Profitabilitas Perusahaan Tambang dan Energi Dalam Indeks ISSI Tahun 2019–2023 - Safitri, Junaidi (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2025)
This study aims to analyze the factors that influence the profitability of mining and energy companies listed in the Indonesian Sharia Stock Index (ISSI) in the period 2019–2023. The variables used as measurements in this study include Green Investment, Enterprise Value (EV), Capital Expenditure (CAPEX), and Shares Outstanding, in determining profitability. This study uses a quantitative approach with a panel data regression method to analyze secondary data obtained from financial statements and company environmental performance reports. The results of the analysis show that green investment has a significant positive effect on company profitability, indicating that the implementation of sustainable investment can improve competitiveness and operational efficiency. The Enterprise Value variable also has a significant positive effect, while Capital Expenditure shows a significant negative effect on profitability, reflecting the potential impact of financial burdens in the short term. Meanwhile, Shares Outstanding also shows a significant negative effect on profitability. This study provides an important contribution to the literature related to sustainable investment, especially in strategic sectors such as mining and energy. The results of this study also provide practical recommendations for investors and policy makers to further encourage the implementation of green investment as a strategy towards economic and environmental sustainability.